The genus Sesuvium (Aizoaceae, Sesuvioideae) in the Southern Cone - Minué, Carlos (2021)
Sesuvium is a genus of 14 to 17 species of succulent plants, both annual and perennial, widely distributed in tropical and subtropical regions. The genus Sesuvium has not yet been studied in detail in the Southern Cone (Argentina, Southern Brazil, Chile, Paraguay and Uruguay), which has led to a misidentification of numerous specimens as S. portulacastrum. As part of the ongoing floristic, taxonomic and ecologic studies in Argentina, we revise the genus Sesuvium for the Southern Cone. This study is based on field investigation, examination of herbarium specimens, and revision of literature. The taxonomic treatments, maps of distribution, detailed descriptions, photographs, an illustration, a dichotomous key and a comparative table to differentiate the species of the genus Sesuvium occurring in the Southern Cone are presented. Finally, ecological, morphological, and taxonomic aspects of the species are discussed. The new combination of S. americanum (≡ Trianthema americanum Gillies ex Arn.; = S. verrucosum Raf.) is proposed. Lectotypes for three names are here designated (S. revolutifolium Vahl ex Willd.; S. revolutifolium Lam., and S. parviflorum DC.). Four species should be accepted for the Southern Cone: S. americanum, S. humifusum, S. mezianum and S. sessile. Furthermore, S. portulacastrum is excluded from the flora of the Southern Cone.